Seleksi Resistansi Wereng Batang Padi Coklat terhadap Insektisida Fipronil - Melhanah Melhanah; Witjaksono Witjaksono; Y. A. Trisyono (Universitas Gadjah Mada, 2002)
The rice brown planthoper, Nilaparvata lugens Stal (Homoptera: Delphacidae), is one of key pests on rice. The use of insecticides unwisely has caused N. lugens to develop resistance. The objective of this research was to determine the potency of N. lugens to develop resistance through laboratory, selections to fipronil, a relatively new insecticide. A population of N. lugens was collected from rice field in Muntilan, Central Java during the outbreak in 2001. Selections were carried out every generation for four generations against third instars. Selection was started by dipping Cisadane rice seedlings in a solution of fipronil (50 ppm). The concentration was increased every generation, and the concentration used for the last selection (the fourth generation) was 250 ppm. To determine the rate of resistance development, biassays were carried out to estimate LC50 of fipronil against selected and non-selected populations of N. lugens, and their LC50 values were compared to that of the laboratory population. The laboratory population has been in the laboratory for 15 years without any insecticides exposure. The founding population was as susceptible as the laboratory population to fipronil because their LC50 values were similar. Even though the concentration for selections was increased from generation to generation, the survival rate of N. lugens increased steadily. After four generations of selection, the resistance of selected population was 27.3 times than the non-selected population. These findings indicate that N. lugens population has the potency to develop resistance to fipronil in a continuous selection pressure is applied.